HIV-related Merkel cell carcinoma: A report of three cases from the UK. (October 2022) - Panou, Evdoxia; Nikolaou, Christos; Payagala, Sashini; Bakkour, Waseem; Shaw, Heather; Perrett, Conal; French, Patrick; Ratynska, Marzena; Brock, Cathryn; Rayment, Michael; Bunker, CB
Merkel cell carcinoma (MCC) of the skin is a rare, aggressive and often fatal neuroendocrine skin cancer. The incidence of MCC has significantly increased in the last decades. Factors that have been associated with the development of MCC include infection with Merkel Cell polyomavirus (MCPyV), ultraviolet exposure, hematologic malignancies and immunosuppression.We present three cases of patients living with HIV who were diagnosed with MCC. HIV cases associated with MCC have been rarely reported and to our knowledge, not yet before in the UK.